2023
DOI: 10.1002/met.2132
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the occurrence of thermal seasons in Poland in 1961–2020

Abstract: The article analyses the variability of thermal seasons in Poland in 1961–2020. Based on the average monthly air temperature values from 55 stations, the onset and end dates as well as the duration of the six thermal seasons were calculated. Taking into account the thermal thresholds of 0°C, 5°C and 15°C for each year, early spring, spring, summer, autumn, early winter and winter can be distinguished. A significant spatial differentiation of the dates of the beginning and duration of the thermal seasons in Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…According to research, the trend of moving the starting date of the growing season has been consolidated with increasingly earlier occurrences. In the last 30 years (1991-2020), as compared with 1961-1990, there was an acceleration in the occurrence of the beginning of the thermal spring season (initiating the growing season) by as much as a month in the west, and by two weeks in the east of Poland [28]. Szyga-Pluta et al [29] found an increase in the length of the growing season in Poland by an average of 4.8 days over 10 years between 1966 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…According to research, the trend of moving the starting date of the growing season has been consolidated with increasingly earlier occurrences. In the last 30 years (1991-2020), as compared with 1961-1990, there was an acceleration in the occurrence of the beginning of the thermal spring season (initiating the growing season) by as much as a month in the west, and by two weeks in the east of Poland [28]. Szyga-Pluta et al [29] found an increase in the length of the growing season in Poland by an average of 4.8 days over 10 years between 1966 and 2020.…”
Section: Resultsmentioning
confidence: 99%